TECHNICAL ANALYSIS IN STOCK PRICE MOVEMENTS USING THE HISTORICAL PRICE METHOD AND CHART PATTERN IN THE ENERGY SECTOR INDUSTRY IN THE COMING YEAR - Hikmah, Husnul; Wahyu, Didin Rasyidin; Yuliah, Yuliah (International Research of Multidisciplinary Analysis, 2024)
The capital market plays a very important role in long-term investments. However, the capital market often also involves high risks because it depends on market price movements that cannot be predicted with certainty. The most popular financial instruments in the capital market are stocks. This stock is used by investors to gain profit. In the world of investing, there are two ways to analyze stocks: technical analysis and fundamental analysis. Technical analysis examines past stock price patterns to predict future price directions, without considering the company's conditions. Meanwhile, fundamental analysis looks at factors such as company management and financial performance to estimate the future value of the stock. Out of 81 companies in the energy sector that were evaluated, 22 companies are experiencing an uptrend. Using chart patterns, there are five companies, namely Adaro Energy Indonesia (ADRO), Trans Power Marine Tbk (TPMA), Delta Dunia Makmur (DOID), Elnusa Tbk. (ELSA), and Resource Alam Indonesia Tbk (KKGI), among those predicted to continue experiencing positive growth in the future. The use of candlestick charts and the Exponential Moving Average (EMA) indicator has helped in identifying upward trends in stock prices. In addition, chart pattern methods, particularly the Cup and Handle and Inverted Head and Shoulders patterns, provide additional insights into the potential continuation of bullish trends in several energy sector companies. The analysis of this graphic pattern allows investors to project stock price movements more accurately, aiding in making more informed investment decisions